2018
DOI: 10.2139/ssrn.3279345
|View full text |Cite
|
Sign up to set email alerts
|

Are Rights Out of Time? International Human Rights Law, Temporality, and Radical Social Change

Abstract: Human rights were a defining discourse of the twentieth century. The opening decades of the twenty-first, however, have witnessed increasing claims that the time of this discourse as an emancipatory tool is up. Focusing on international human rights law, I offer a response to these claims. Drawing from Elizabeth Grosz, Drucilla Cornell and Judith Butler, I propose that a productive future for this area of law in facilitating radical social change can be envisaged by considering more closely the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…How do we make sense of the connection between law and time? Scholars have suggested that the law serves to construct ideas of time (McNeilly, 2018) and sustains competing temporalities: it is both certain through its enactment at a specific point in time and uncertain due to the potential of reversibility (McNeilly, 2018, p. 4). Despite its ability to hold plural histories and futures, the legal system is largely stagnant and backward gazing where discourses of gender and sexuality are concerned.…”
Section: Resultsmentioning
confidence: 99%
“…How do we make sense of the connection between law and time? Scholars have suggested that the law serves to construct ideas of time (McNeilly, 2018) and sustains competing temporalities: it is both certain through its enactment at a specific point in time and uncertain due to the potential of reversibility (McNeilly, 2018, p. 4). Despite its ability to hold plural histories and futures, the legal system is largely stagnant and backward gazing where discourses of gender and sexuality are concerned.…”
Section: Resultsmentioning
confidence: 99%
“…In paying empirical attention to the relation between legal practices of sorting time and the definition of violence, we can understand how the court closes off routes to alternative futures, thereby sustaining forms of structural violence. Nevertheless, law has the opportunity to sort and include temporality in a different way, leaving space for alternative ways of knowing or predicting the future (McNeilly, 2019). This subsection has therefore emphasized what is at stake in terrorism-financing proceedings, highlighting how empirical accounts of time can offer forms of legal resistance that create space for the inclusion of multiple pasts, presents and futures (McNeilly, 2019).…”
Section: What Counts As Violence?mentioning
confidence: 99%
“…Nevertheless, law has the opportunity to sort and include temporality in a different way, leaving space for alternative ways of knowing or predicting the future (McNeilly, 2019). This subsection has therefore emphasized what is at stake in terrorism-financing proceedings, highlighting how empirical accounts of time can offer forms of legal resistance that create space for the inclusion of multiple pasts, presents and futures (McNeilly, 2019).…”
Section: What Counts As Violence?mentioning
confidence: 99%
“…Time, Temporality and Legal Judgment is the most recent contribution to what its author Tanzil Chowdhury describes as the 'nascent "temporal turn" in socio-legal studies, legal anthropology and jurisprudence ' (2020: 145). Chowdhury is correct that socio-legal scholars have increasingly turned their attention to time and have begun to offer a range of new ways to understand law, legal processes, institutions and discourses through this lens (Beynon-Jones and Grabham, 2018;Grabham, 2016;Keenan, 2013;McNeilly, 2019;Mawani, 2014). This work has revealed a variety of ways in which law produces time and how legal times connect to the social (Greenhouse, 1989).…”
mentioning
confidence: 99%